Predicting the Future Distribution of Leucobryum aduncum under Climate Change - Puwadol Chawengkul; Patsakorn Tiwutanon; Nuttha Sanevas; Ekaphan Kraichak (Diversity, 2024)
Leucobryum aduncum is a moss species reported in many Southeast Asian regions, often found in forests with a high humidity. Climate change may impact the future distribution of this species. This study aimed to model the current distribution and predict the impact of climate change on L. aduncum distribution in the next 50 years across Southeast Asia. In the process, relevant climate variables in the distribution of the species were also identified. The occurrence data of this species with current and future climate models from CMIP6 under moderate (SSP2) scenarios were used to predict current and future L. aduncum distributions. Under the current climate, the predicted suitable areas for L. aduncum included most mountainous areas. However, many Southeast Asian areas showed a lower probability of finding this species in the next 50 years. The distribution area of this species will dramatically decrease by 50.16% in the current area. The most important ecological variables included the “mean temperature of the driest quarter” and the “annual temperature range”. This study suggests the possible impacts of an increased temperature and the scale of climate change on the distribution of sensitive plants like bryophytes.